Reinterpretasi atas QS. al-Baqarah [2]: 234 perspektif Ma’nā-cum-Maghzā - Muhammad, Azuma (Sunan Kalijaga Islamic State University, 2023)
Classical interpretations that often see ‘iddah as simply a waiting period to avoid new marriages or certain activities reduce the complexity of deeper meaning. This is complicated by the increasing role of women today in the public sphere. Thus, encouraging researchers to reinterpret the concept of ‘iddah in Q.S. al-Baqarah [2]: 234. To achieve this goal, this study uses a qualitative method with ma’nā-cum-maghzā theory as an analytical tool. This study shows that Q.S. al-Baqarah [2]: 234 is a verse that talks about efforts to provide a safe space for women to mourn and cope with the loss of a husband. In addition, ‘iddah also serves to protect women from the shackles of social constructions that may be burdensome and harmful. In the context of Islamic law, ‘iddah also provides legal relief that helps women to deal with difficult situations more securely. Last but not least, the authentication of lineage regardless of changing social norms as times evolve must be maintained. Moreover, this verse encourages people to play an active role as agents of social transformation.